Fatigue in tennis: Mechanisms of fatigue and effect on performance - Hornery, D. J.; Farrow, D.; Mujika, I.; Young, W. (Sports Medicine, 2007)
This article reviews research sourced through sport science and medical journal databases (SportDiscus(R) and PubMed) that has attempted to quantify the effects of fatigue on tennis performance. Specific physiological perturbations and their effects on common performance measures, such as stroke velocity and accuracy, are discussed. Current literature does not convincingly support anecdotal assertions of overt performance decrements during prolonged matches or matches played during unfavourable (e.g. hot and humid) environmental conditions. The constraints of field-based research have presented, and continue to present, a methological challenge to investigators within this domain. Limitations of previous investigations have included the following: (i) a restricted measurement approach to the mulifaceted skills that form the basis of match performance; (ii) a lack of sensitivity and large variability in skill or performance measures; (iii) usage of non tennis-specific methods to induce fatigue; and (iv) fatigue levels failing to reflect those recorded in match play.